Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1016/j.neuint.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vinpocetine on mitochondrial function and neuroprotection in primary cortical neurons

Abstract: Effects of Vinpocetine on mitochondrial function and neuroprotection in primary cortical neurons Tarnok, K.; Kiss, E.; Luiten, P. G. M.; Nyakas, C.; Tihanyi, K.; Schlett, K.; Eisel, U. L. M.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Although it binds with a moderate affinity to TSPO, compared to ligands with nanomolar-sub-nanomolar binding affinities to TSPO, due to its favourable brain penetration it can be a usable PET radioligand for in vivo exploration of the TSPO system in human brain . Furthermore, Tárnok et al (2008) have recently demonstrated that vinpocetine exerts a neuroprotective action by decreasing cortical mitochondrial inner membrane potential in rats strengthening the hypothesis, that vinpocetine acts via the TSPO system.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Although it binds with a moderate affinity to TSPO, compared to ligands with nanomolar-sub-nanomolar binding affinities to TSPO, due to its favourable brain penetration it can be a usable PET radioligand for in vivo exploration of the TSPO system in human brain . Furthermore, Tárnok et al (2008) have recently demonstrated that vinpocetine exerts a neuroprotective action by decreasing cortical mitochondrial inner membrane potential in rats strengthening the hypothesis, that vinpocetine acts via the TSPO system.…”
Section: Introductionmentioning
confidence: 66%
“…The agent is widely used as a neuroprotective drug in the prevention and treatment of cerebrovascular diseases (Bereczki and Fekete, 2000;Nagy and Simon, 2004;Onishchenko et al, 2008;Fehér et al, 2009). In addition to its widely studied neuroprotective effects (Bönöczk et al, 2000;Tárnok et al, 2008;Nyakas et al, 2009) it is a well known phospho-diesterase (PDE) inhibitor (Dunkern and Hatzelmann, 2007;Deshmuk et al, 2009;Wunder et al, 2009) and voltage dependent sodium channel inhibitor (Ádám-Vizi, 2000). Most recently Jeon et al (2010) reported that vinpocetine is a potent antiinflammatory agent by targeting an IκB-related Kinases (IKK) dependent mechanism (cfr.…”
Section: Introductionmentioning
confidence: 99%
“…65 Briefly, embryonic cortices were incubated in 0.05% trypsin solution (Gibco, Life Technologies, R001100) for 15 min at 37 C. After a brief centrifugation step, cells were triturated in NeuroBasal media (Gibco, Life Technologies, 21103-049) supplemented with B27 (Gibco, Life Technologies, A24775-01), 0.5 mM Glutamax (Gibco, Life Technologies, 10567014), 40 mg/ml gentamycin and 2.5 mg/ml amphotericin B (Sigma, Y0000005), and filtered through a sterile polyester mesh with 42 mm pore size (EmTek Ltd, S72210-SS). Cells were seeded onto poly-D-lysine (PDL; Sigma, P7405) coated 6 or 96 well plates at 10 6 or 8x10 4 cells/well densities, respectively.…”
Section: Primary Neuronal Cell Culturesmentioning
confidence: 99%
“…Using an in vitro glutamate excitotoxicity model, Tarnok et al [30] have investigated the anti-neurodegenerative effect of vinpocetine, a drug extracted by Vinca minor, and widely used for the treatment of cerebrovascular disorders and cognitive impairment. Vinpocetine, which has a significant binding affinity to TSPO, has been tested alone or in combination with PK11195 and Ro5-4864 in parallel experiments.…”
Section: Tspo Ligands In the Treatment Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…It has been reported that vinpocetine is more efficacious in exerting a neuroprotective action in glutamate-injured mouse primary cortical neuron, with respect to classic TSPO ligands alone, although, at subcellular levels, Ro5-4864 has proven to be more effective in preserving normal mitochondrial membrane potential than vinpocetine. Interestingly, the combined cell treatment with vinpocetine and PK11195, or Ro5-4864, has produced an increase in neuroprotection [30].…”
Section: Tspo Ligands In the Treatment Of Neurodegenerative Diseasesmentioning
confidence: 99%